Detection and mitigation of actuator attacks on small unmanned aircraft systems. (February 2019) - Muniraj, Devaprakash; Farhood, Mazen
Abstract: Unmanned aircraft systems (UAS) are susceptible to malicious attacks originated by intelligent adversaries, and the actuators constitute one of the critical attack surfaces. In this paper, the problem of detecting and mitigating attacks on the actuators of a small UAS is addressed. Three possible solutions of differing complexity and effectiveness are proposed to address the problem. The first method involves an active detection strategy, whereby carefully designed excitation signals are superimposed on the control commands to increase the detectability of the attack. In the second method, an unknown input observer is designed, which in addition to detecting the attack also estimates the magnitude of the attack. The third method entails designing an actuator system that makes use of variable frequency pulse-width modulated signals to improve the resilience of the actuator against malicious attacks. The effectiveness of the proposed methods is demonstrated using flight experiments and realisticMATLAB simulations that incorporate exogenous disturbances, such as steady winds, atmospheric turbulence, and measurement noise. Highlights: Actuators constitute one of the critical attack surfaces for small unmanned aircraft. A software approach and a resilient hardware approach are proposed. The software approach involves developing algorithms for attack detection. The hardware approach focuses on designing actuators that are resilient to attacks. Realistic simulations and flight experiments show the effectiveness of the methods.